If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-7q + 1) = -5(10 + -9q) + q Reorder the terms: -1(1 + -7q) = -5(10 + -9q) + q (1 * -1 + -7q * -1) = -5(10 + -9q) + q (-1 + 7q) = -5(10 + -9q) + q -1 + 7q = (10 * -5 + -9q * -5) + q -1 + 7q = (-50 + 45q) + q Combine like terms: 45q + q = 46q -1 + 7q = -50 + 46q Solving -1 + 7q = -50 + 46q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-46q' to each side of the equation. -1 + 7q + -46q = -50 + 46q + -46q Combine like terms: 7q + -46q = -39q -1 + -39q = -50 + 46q + -46q Combine like terms: 46q + -46q = 0 -1 + -39q = -50 + 0 -1 + -39q = -50 Add '1' to each side of the equation. -1 + 1 + -39q = -50 + 1 Combine like terms: -1 + 1 = 0 0 + -39q = -50 + 1 -39q = -50 + 1 Combine like terms: -50 + 1 = -49 -39q = -49 Divide each side by '-39'. q = 1.256410256 Simplifying q = 1.256410256
| 64t^2+t-16=0 | | (x+3)(x+12)=2x | | Y=2x^2-5x-11 | | x-1+6=4 | | -4(-9y+2)+2=-7-6y | | 70x+60y=161000 | | -64=-15-4 | | Y=200+150+50-30 | | 7y+11=2-2y | | 3(x+3)-4x=4 | | 4(2w-1)-3w=7w+24+5w | | 3r-(8-5r)=-6 | | -2(k-3)=-12 | | 23k-3=3k+7 | | 3y+12-7y=-4 | | 6h+100+10=16h-10h+110 | | -5n-2(2n-4)=-6n+1 | | 6x+x=46242 | | u^2+9u+8=0 | | 6h+100+10=16h-1h+110 | | 6p^3+5p^2+p=0 | | -5n-2n(2n-4)=-6n+1 | | -4=2x^2-5x-11 | | -35=7t | | r-92=215 | | 10n+21=25-2n | | 8=n+10 | | 3m-7=5m-9 | | 3m-7=53-9 | | c^2+c-64=0 | | 8-b=2-3b | | 6y=196 |